2012
DOI: 10.1177/0363546512446928
|View full text |Cite
|
Sign up to set email alerts
|

Individualized Anterior Cruciate Ligament Surgery

Abstract: Anatomic double-bundle reconstruction is not superior to anatomic single-bundle reconstruction when an individualized ACL reconstruction technique is used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
60
2
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 130 publications
(69 citation statements)
references
References 46 publications
0
60
2
7
Order By: Relevance
“…The basic concept of anatomic ACL reconstruction and its procedures were recently reported in detail 53-55 . The surgical procedure is briefly described here.…”
Section: Methodsmentioning
confidence: 99%
“…The basic concept of anatomic ACL reconstruction and its procedures were recently reported in detail 53-55 . The surgical procedure is briefly described here.…”
Section: Methodsmentioning
confidence: 99%
“…41,42 Its potential clinical importance is exemplified by patients with possible combined ACL and ALL rupture who do not progress satisfactorily after isolated ACL reconstruction. 23,24 A recent anatomic study performed also suggested that a difference between the ALL in males and females might exist. 37 …”
mentioning
confidence: 99%
“…3,9,22 Although numerous advances have been made in surgical reconstruction techniques and graft choices, it is well recognized that some patients continue to experience persistent rotatory knee instability after ACL reconstruction. 16,17,34,36 It has been suggested that failure to address additional secondary stabilizers may contribute to this postoperative instability. In fact, unaddressed meniscal tears, underappreciated meniscocapsular injuries, increased posterior tibial slope, and anterolateral capsular injuries have all been demonstrated to play a role in rotatory knee stability.…”
mentioning
confidence: 99%